2003
DOI: 10.1149/1.1577543
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mn Dissolution from LiMn[sub 2]O[sub 4] Spinel Electrodes Using Rotating Ring-Disk Collection Experiments

Abstract: The goal of this research was to measure Mn dissolution from a thin porous spinel LiMn 2 O 4 electrode by rotating ring-disk collection experiments. The amount of Mn dissolution from the spinel LiMn 2 O 4 electrode under various conditions was detected by potential step chronoamperometry. The concentration of dissolved Mn was found to increase with increasing cycle numbers and elevated temperature. The dissolved Mn was not dependent on disk rotation speed, which indicated that the Mn dissolution from the disk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 26 publications
5
88
0
Order By: Relevance
“…15 Although less susceptible than spinel, metal dissolution does occur in NCM electrodes and has been implicated in a rise in impedance and capacity fade with cycling. 4,16 Two main routes by which capacity fading may occur due to dissolution are (i) structural changes to the positive electrode and leading to reduced insertion capacity and (ii) accelerated growth of the SEI layer at the negative electrode and the resulting irreversible Li consumption.…”
Section: 7-14mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Although less susceptible than spinel, metal dissolution does occur in NCM electrodes and has been implicated in a rise in impedance and capacity fade with cycling. 4,16 Two main routes by which capacity fading may occur due to dissolution are (i) structural changes to the positive electrode and leading to reduced insertion capacity and (ii) accelerated growth of the SEI layer at the negative electrode and the resulting irreversible Li consumption.…”
Section: 7-14mentioning
confidence: 99%
“…4,16 Two main routes by which capacity fading may occur due to dissolution are (i) structural changes to the positive electrode and leading to reduced insertion capacity and (ii) accelerated growth of the SEI layer at the negative electrode and the resulting irreversible Li consumption. 15,[17][18][19][20][21][22] Capacity fade due to the structural changes occurring in the positive electrode during partial dissolution is more likely in spinel electrodes, where the extent of dissolution is high, or at high potentials (overcharge). This large degree of dissolution in spinels may cause shrinkage of the active material, which decreased the effective transport properties and kinetics of the electrode.…”
Section: 7-14mentioning
confidence: 99%
“…6 Mn dissolution and severe strain from Jahn-Teller distortion. 3,56,57 In addition, it has been reported that the Mn dissolution of LiMn 2 O 4 spinel is oen accelerated with larger specic surface area, 58,59 which should be also applicable to LiNi 0.5 -Mn 1.5 O 4 , a derivative of LiMn 2 O 4 . The impurity phase tends to react with the electrolyte and thus causes capacity fading.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Consideringt he different degradation effects of Mn-based spinel materials,t he capacity fadingo fL MO because of Mn dissolution into the electrolyte during cycling was studied extensively. [10,12,[45][46][47][48][49][50][51] Mn dissolution is driven mainly by the disproportionation reaction, which implies the transformation of Mn 3+ + ions into soluble Mn 2+ + and as table Mn 4+ + compound. [45,51] Thed isproportionation of Mn is hinderedi n LNMO because of the reduced Mn 3+ + content in the presence of Ni 2+ + .F urthermore,t he introduction of Ni leads to the enhanceds tability of the delithiated structure in the charged state [11] compared to that of LMO,w hich suffers from structural changes accompanied with the dissolution of Mn.…”
Section: Introductionmentioning
confidence: 99%
“…[45,51] Thed isproportionation of Mn is hinderedi n LNMO because of the reduced Mn 3+ + content in the presence of Ni 2+ + .F urthermore,t he introduction of Ni leads to the enhanceds tability of the delithiated structure in the charged state [11] compared to that of LMO,w hich suffers from structural changes accompanied with the dissolution of Mn. [46] Additionally,during discharge at high rates,the fastlithiation of the active material leads to an accumulation of Li ions on the surface of the particles. [52] In LMO,t his can cause the average Mn valence to fall below + +3.5, and the onset of Jahn-Teller distortion leads to as pontaneous increase of the unit cell by 16 %.…”
Section: Introductionmentioning
confidence: 99%